2022
DOI: 10.1038/s41598-022-05787-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient micropropagation of Thunbergia coccinea Wall. and genetic homogeneity assessment through RAPD and ISSR markers

Abstract: Thunbergia coccinea Wall. ex D. Don being a rare, ornamental and medicinal plant of India, is needed to propagate for conserving the germplasm and analyzing its phytochemical compounds in the future. A reliable protocol for direct in vitro propagation using nodal shoot meristem of T. coccinea as explant was standardized. The highest number of shoots per explant (22.17 ± 0.54) with maximum shoot length (2.36 ± 0.28) in cm was obtained in Murashige and Skoog (MS) medium supplemented with 9.70 µM of 6-furfurylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…In our study, ISSR primers revealed that all the ex-vitro-established micropropagated plants were genetically identical to the donor plant, indicating that genetic homogeneity had been maintained across the regenerants. Similar studies on the genetic stability of regenerated plants using the ISSR molecular marker have been reported before in Bacopa monnieri [80], Ruta graveolens [19], Morus alba [81], Rauwolfia tetraphylla [82], Ficus carica [83], Flemingia macrophylla [84], Solanum khasianum [85], and Thunbergia coccinea [86].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, ISSR primers revealed that all the ex-vitro-established micropropagated plants were genetically identical to the donor plant, indicating that genetic homogeneity had been maintained across the regenerants. Similar studies on the genetic stability of regenerated plants using the ISSR molecular marker have been reported before in Bacopa monnieri [80], Ruta graveolens [19], Morus alba [81], Rauwolfia tetraphylla [82], Ficus carica [83], Flemingia macrophylla [84], Solanum khasianum [85], and Thunbergia coccinea [86].…”
Section: Discussionsupporting
confidence: 81%
“…The acclimatization of in vitro regenerated plantlets was a difficult step of the micro-propagation protocol establishment of their susceptibility to fungal diseases 35 . In the present study, well-rooted micro propagated plantlets were removed from the medium, washed, and successfully transplanted into small plastic pots containing sterile soil rites.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study support the maintenance of genetic similarity of direct regenerated plants with the mother plants during the in vitro process. The RAPD and ISSR techniques have been applied widely to examine the genetic homogeneity in various in vitro derived plants, such as Magnolia sirindhorniae (Cui et al, 2019 ), Ranunculus wallichianus (Srinivasan et al, 2021 ), P. africana (Komakech et al, 2020 ), Lillium davidii (Yang et al, 2021 ), and Thunbergia coccinea (Sultana et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%